Vivre avec la mémoire de la catastrophe - Magali Reghezza-Zitt (Éditions en environnement VertigO, 2021)
This paper aims to address the spatiality of disaster memory and show how disaster memory transforms the relationship between the inhabitants, who experienced a crisis, and the lived space. Considering the 1975-1977 eruptive crisis of the Soufrière, we study both the institutional memory and the individual memories of the direct witnesses. We show that forty years later, people still remember events in a sensitive and affect-filled way, which is highly spatialized and has a particular spatiality. Living with the volcano implies to live with the memory of the crisis, which is interpreted by people as a catastrophe. Memory thus produces new territorialities, i.e. new ways of dwelling. Conversely, institutional memory is not very present and does not transform the geographical space in its materiality or its meaning.